Le Rivoluzioni colorate in Eurasia: Georgia, Ucraina e Kyrgyzstan - Fazzi, Patrizia (Cambio. Rivista sulle Trasformazioni Sociali, 2017)
The protests at the turn of the new millennium that have involved Georgia, Ukraine and Kyrgyzstan, defined Color Revolutions, have represented events of particular interest in the debate on the post-soviet transitology. The aim of the essay is to define the subject in its theoretical framework and to examine the main events which led to the fall of the regimes in these countries, in order to find the common thread that joins the cases examined.